Effect of timing of casirivimab and imdevimab administration relative to mRNA-1273 COVID-19 vaccination on vaccine-induced SARS-CoV-2 neutralising antibody responses: a prospective, open-label, phase 2, randomised controlled trial - Isa, Flonza; Gonzalez Ortiz, Ana M; Meyer, Jonathan; Hamilton, Jennifer D; Olenchock, Benjamin A; Brackin, Taylor; Ganguly, Samit; Forleo-Neto, Eduardo; Faria, Lori; Heirman, Ingeborg; Marovich, Mary; Hutter, Julia; et al. (The Lancet infectious diseases, 2025)
Deeper insight is needed on how monoclonal antibodies (mAbs) affect vaccine-mediated immune responses when targeting the same protein. We describe the first prospective randomised trial designed to understand mAb-mediated alterations in vaccine-induced immune responses to SARS-CoV-2 spike protein epitopes. This randomised, open-label, parallel-group study assessed the potential interaction of a mAb combination, casirivimab and imdevimab, with a vaccine, Moderna's mRNA-1273, in healthy SARS-CoV-2 immunologically naive, seronegative adults at six centres in the USA. Participants were randomly assigned (per prespecified randomisation ratios within enrolment waves) according to a computer-generated randomisation scheme, stratified by age (<65 years and ≥65 years), to various intravenous or subcutaneous doses of casirivimab and imdevimab before, after, or at the same time as mRNA-1273 or to mRNA-1273 only. The doses of casirivimab and imdevimab were chosen to mimic various time intervals between receipt of 1200 mg of the mAb and the first dose of a primary series with mRNA-1273. The primary endpoint was vaccine-induced 50% inhibitory dilution neutralising antibody titres to SARS-CoV-2 spike protein, 56 days after the first vaccination. Secondary endpoints included vaccine-induced total antibodies to SARS-CoV-2 antigens and incidence of treatment-emergent adverse events. Exploratory endpoints included blood-derived T-cell and B-cell responses. The per-protocol set was used for the analysis of the primary endpoint and included all randomly assigned participants who received both doses of the vaccine and completed the injection or infusion of casirivimab and imdevimab per protocol, had no evidence of SARS-CoV-2 infection in the past or in the 56 days after the first dose of vaccine, and did not receive any intervention outside of the study that could alter the immune response. Safety was assessed in the safety analysis set, which included all randomly assigned participants who had received one or more doses of mRNA-1273 or any study drug, and analysed based on treatment received. The study is registered with ClinicalTrials.gov, NCT04852978, and is complete. Between April 29, 2021, and Nov 21, 2022, 807 participants were assessed for eligibility and 295 were randomly assigned. 293 participants were included in the safety analysis set and 260 were included in the per-protocol set. All vaccinated participants developed neutralising antibodies to SARS-CoV-2, with median titres above the published protective threshold (100 IU/mL) against the SARS-CoV-2 D614G variant (considered a reference strain at the time the initial COVID-19 vaccines were developed). Titres were decreased up to 4-fold (median titres 280–450 IU/mL for casirivimab and imdevimab vs 1160 IU/mL for vaccine only on day 56) when casirivimab and imdevimab was given 85 days or less before vaccination (150–1200 mg intravenously) or co-administered subcutaneously (600 mg or 1200 mg) with vaccination. Minimal reduction in neutralisation titres was observed in the 48 mg and 12 mg intravenous groups, corresponding to receipt of casirivimab and imdevimab 113 days and 169 days, respectively, before vaccination, and when administering the vaccine 6 days before the mAb. Across all groups, mAbs had a minimal effect on vaccine-induced total antibodies and T-cell responses to the spike protein. Casirivimab and imdevimab plus mRNA-1273 was generally well tolerated; a slight increase in treatment-emergent adverse events was observed in the casirivimab and imdevimab plus vaccine groups versus the vaccine-only group. Casirivimab and imdevimab administration before or at the time of COVID-19 vaccination reduced the elicitation of SARS-CoV-2 neutralising antibodies, but minimal effect was observed when vaccination occurred before mAb administration. Although the clinical significance of this decrease in neutralisation is unclear, this evidence suggests that further investigation of potential interactions could be warranted before concurrent clinical use of mAbs and vaccines targeting the same viral proteins as their main modes of action for the prevention or treatment of infectious diseases. Regeneron Pharmaceuticals and F Hoffmann-La Roche.